WYPRAWA CESARZA SEPTYMIUSZA SEWERA DO BRYTANII W LATACH 208-211 W ŚWIETLE ŹRÓDEŁ HISTORIOGRAFICZNYCH I NUMIZMATYCZNYCH - Janiszewska-Sieńko, Daria (In Gremium. Studies in History, Culture and Politics, 2012)
THE 208-211 EXPEDITION OF EMPEROR SEPTIMIUS SEVERUS TO BRITAIN IN HISTORIOGRAPHICAL AND NUMISMATIC SOURCES The expedition emperor Septimius Severus made to Britain in years 208-211 was the last military campaign in the life of this first representative of the Severus dynasty. Its impact can be found in nu- merous historiographical, numismatic and inscriptive sources. This article deals with the comparison of the little source material found in the works of Roman historians Cassius Dio and Herodian with the information passed on to us by the imperial mint. The campaign had a few objectives. First of all, it aimed at taming the rebellious Caledonian people living in northern Britain, putting the administration in Roman Britain in order and rebuilding the local limes. The emperor’s desires to strengthen his image of a victorious leader and to clearly mark his sons Karakalla and Geta as his successors were also important. The fights with the locals did not have a tangible effect (the Romans failed to subdue the whole of Britain) but undoubtedly had a propaganda character as planned by the emperor. Septimius Severus died at the beginning of 211 in Eburacum and not long after his sons ended the campaign and went back to Rome as equal emperors of Imperium Romanum.